A high conductivity ultrathin anion-exchange membrane with 500+ h alkali stability for use in alkaline membrane fuel cells that can achieve 2 W cm−2 at 80 °C. Issue 31 (27th July 2018) - Wang, Lianqin; Bellini, Marco; Miller, Hamish A.; Varcoe, John R.
Abstract : This article describes the development of a sub-30 μm thick LDPE-based radiation-grafted anion-exchange membrane (RG-AEM) with high performance characteristics when fully hydrated. Abstract : This article describes the development of a sub-30 μm thick LDPE-based radiation-grafted anion-exchange membrane (RG-AEM) with high performance characteristics when fully hydrated. This RG-AEM had a OH − anion conductivity of 200 mS cm −1 (80 °C in 100% relative humidity (RH) environments), which led to a H2 /O2 anion-exchange membrane fuel cell (AEMFC) performance of 2.0 W cm −2 (80 °C, RH = 92% environments, a PtRu/C anode, and a Pt/C cathode) and a H2 /air (CO2 -free) AEMFC peak power density of 850 mW cm −2 with a (non-platinum-group) Ag/C cathode electrocatalyst. When hydrated in a RH = 100% N2 (CO2 -free) atmosphere, the OH − form of this RG-AEM shows <7% degradation after 500 h at 80 °C, with the extent of degradation being highly similar to that when measured using three different techniques (decrease in conductivity, decrease in ammonium content as measured using Raman spectroscopy, and decrease in ion-exchange capacity).